POETIC CARTOGRAPHIES IN O TURISTA APRENDIZ AND REMATES DE MALES, BY MÁRIO DE ANDRADE: A CRITICAL READING OF MODES OF SPATIAL REPRESENTATION (Editora Impacto Científico, 2025)
This study analyzes the relationship between literature, travel, and the Amazonian imaginary in the modernist work of Mário de Andrade, focusing on The Apprentice Tourist (O turista aprendiz) and Remate de Males. The journey to Northern Brazil undertaken in the 1920s is understood not merely as a geographical displacement, but as an aesthetic, cultural, and intellectual experience that underpins a literary project aimed at reinventing Brazil. The research examines how elements of Amazonian culture—landscapes, peoples, practices, and the historical tensions of the Upper Solimões region—are incorporated and reworked in travel prose and poetry, shaping a sensitive cartography that articulates the local and the universal. Grounded in the theoretical contributions of Antonio Candido, Paul Ricoeur, and Ana Pizarro, the study conceives the literary work as a living system in which author, text, and reader are interconnected. It concludes that Mário de Andrade constructs a representation of the Amazon that goes beyond ethnographic or touristic records, transforming it into poetic matter and a symbolic space for reflecting on identity, otherness, and nationhood, thereby expanding the boundaries of Brazilian modernist literature.DOI: https://doi.org/10.56238/edimpacto2025.090-074